Adherence and blood pressure control in hypertensive patients: a cross-sectional study - Intan Sukma Larasati; Eva Nurinda; Ari Susiana Wulandari; Nurul Kusumawardani; Sofyan Indrayana; Danang Prasetyaning Amukti (Faculty of Pharmacy, Universitas Pancasila, 2026)
In 2023, the prevalence of hypertension in the Special Region of Yogyakarta was 31.8%, with 24% of patients inconsistent adherence to therapy. This study was a cross-sectional study which examined the link between adherence to medication and lifestyle changes with blood pressure control among 120 hypertensive patients in the Hypertension Class Program at Bambanglipuro Primary Health Center using an adherence questionnaire. Most participants exhibited low adherence to both medication (54.2%) and lifestyle interventions (73.3%). The cut-off point for grouping respondents into low and high adherence is based on the median value of the respondents' questionnaire scores (because the data is not normally distributed). Uncontrolled blood pressure was prevalent, with a mean systolic pressure of 151.95±11.45 mmHg and a mean diastolic pressure of 87.14±10.45 mmHg. Spearman's rho analysis revealed a statistically significant relationship between adherence and blood pressure control (p<0.001), with a strong negative correlation observed for medication adherence (r = -0.530) and a moderate negative correlation for lifestyle adherence (r = -0.404). Furthermore, low adherence was associated with a substantially increased risk of uncontrolled blood pressure, with odds ratios of 11.30 (95% CI: 4.70–27.21) for medication adherence and 6.82 (95% CI: 2.77–16.80) for lifestyle adherence. These findings underscore the critical importance of improving patient adherence to both pharmacological and non-pharmacological management strategies to achieve optimal blood pressure control.